I like the unpath best: Art-practice-writing and the creation of complex, generative and complicating forms and contexts. (1st September 2017) - Thomson, Amanda
Situating myself as a visual artist with a multimodal practice, this article will explore the relationship of writing to making, using the relationship of writing to my own practice to explore questions relating to research processes, the volume of information gathered and the insertion of other disciplinary perspectives. Here, I will address the element of my practice that is based in landscape, specifically explorations that begin with the idea that places are multilayered, ever-changing, embodied and always active. In seeing places as experiential fields of investigation, writing can add a more complex dimension as it flows from the landscape itself and research about it, to practice, with writing occasionally becoming the artform itself.